0373 Effects of Suvorexant on Sleep in Fibromyalgia. (12th April 2019) - Koshorek, Gail; Verkler, Jelena; Withrow, Dana; Roth, Thomas; Roehrs, Timothy
Abstract: Introduction: The chronic pain disorder, fibromyalgia, is associated with sleep disturbance, typically sleep maintenance. Pharmacological treatment studies have either focused on the pain or the sleep disturbance with equivocal results in that few studies have improved both sleep and pain. No studies have evaluated the effect of sleep medication on pain sensitivity. Suvorexant, an orexin antagonist, approved for treatment of insomnia may provide benefit for both the sleep and pain of fibromyalgia.. Here we report on suvorexant's sleep effects in patients with fibromyalgia and comorbid insomnia disorder gathered as part of a feasibility study. Methods: Women, 21- 65 yrs old, with fibromyalgia and co-morbid insomnia (n=10) were treated for 9 nights with suvorexant, 20 mg, and placebo with the order of the treatments counterbalanced. They were in good psychiatric and stable physical health and met American College of Rheumatology criteria for fibromyalgia and DSM-V criteria for insomnia. On a screening 8-hr PSG other primary sleep disorders were ruled out. On nights 8 and 9 of each treatment 8-hr PSGs were collected. All PSGs were scored following ASSM criteria and PSG measures were compared using repeated measures ANOVAs with night and drug condition as factors. Results: Suvorexant vs placebo increased total sleep time (7.2 vs 6.7 hrs, p< .05) and reduced wake after sleep onset (37 vs 67 min, p<.04) with no night effects or interaction. Suvorexant also reduced wake during the last half (20 vs 41 min, p< .03) and quarter (13 vs 20 min, p< .03) of the night. Latency to persistent sleep and sleep stage measures were not altered by suvorexant. Conclusion: In patients with fibromyalgia and comorbid insomnia disorder suvorexant, 20 mg, improved total sleep time and reduced wake after sleep onset with sustained effects through the last quarter of the sleep period and no alteration of normal sleep staging. Support (If Any): Merck, grant #: 53918, awarded to Dr. Roehrs